2016
DOI: 10.1021/acs.jctc.6b00403
|View full text |Cite
|
Sign up to set email alerts
|

Semiempirical Quantum-Chemical Orthogonalization-Corrected Methods: Benchmarks of Electronically Excited States

Abstract: The semiempirical orthogonalization-corrected OMx methods have recently been shown to perform well in extensive ground-state benchmarks. They can also be applied to the computation of electronically excited states when combined with a suitable multireference configuration interaction (MRCI) treatment. We report on a comprehensive evaluation of the performance of the OMx/MRCI methods for electronically excited states. The present benchmarks cover vertical excitation energies, excited-state equilibrium geometrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 167 publications
5
82
0
Order By: Relevance
“…80 On the theoretical side, one can find a very complete CASPT2/6-31+G(d) investigation of the Morokuma group devoted to the dissociation paths of ketene, 81 as well as an earlier investigation of Szalay and co-workers with CC methods for the same molecule. 82 The structure of the lowest ES structure of diazomethane, constrained in the C 2 v symmetry, was previously determined at both CASPT2/6-31G(d) 26 and CC2/TZVP 25 levels of theory, whereas a CASSCF/6-31G(d) investigation of the ES pathways relating diazirine to diazomethane has also been performed. 83 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…80 On the theoretical side, one can find a very complete CASPT2/6-31+G(d) investigation of the Morokuma group devoted to the dissociation paths of ketene, 81 as well as an earlier investigation of Szalay and co-workers with CC methods for the same molecule. 82 The structure of the lowest ES structure of diazomethane, constrained in the C 2 v symmetry, was previously determined at both CASPT2/6-31G(d) 26 and CC2/TZVP 25 levels of theory, whereas a CASSCF/6-31G(d) investigation of the ES pathways relating diazirine to diazomethane has also been performed. 83 …”
Section: Resultsmentioning
confidence: 99%
“…30–50 atoms) and do not involve the choice of an XCF. However, these methods were reported to overestimate some bond lengths especially for the keto group, 6,22,25,28,41 and caution is necessary before using them as references.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has to be coupled with an appropriate density functional or wave function based approach because it is not able to provide reliable information about the ground state energy surface. It is interesting to note that more sophisticated semi-empirical methods as the OMx-approaches of Thiel and coworkers 91,92 seem to be less suitable. 85 More information about these studies can be found in Section 3.6.…”
Section: Technical Detailsmentioning
confidence: 99%
“…Fulfillment of this task is impossible without comprehensive understanding of the factors underlying the mechanism of action of these devices. In this regard, the methods of analyzing the total electronic density distributions ρ ( r ), such as the quantum theory of atoms in molecules QTAIM and stress tensor analysis methods, can provide complimentary information to the well established approaches analyzing the shape of the potential energy surfaces (PESs) of the ground and excited electronic states of the target compounds . Recently, some of us have developed QTAIM/stress tensor theory for use on the photoisomerization of the retinal chromophore and explored the implications of preferred direction of torsion − φ or + φ of the chromophore upon the photoexcitation …”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the methods of analyzing the total electronic density distributions q(r), such as the quantum theory of atoms in molecules QTAIM [11] and stress tensor analysis methods, can provide complimentary information to the well established approaches analyzing the shape of the potential energy surfaces (PESs) of the ground and excited electronic states of the target compounds. [12][13][14][15][16][17][18] Recently, some of us have developed QTAIM/stress tensor theory for use on the photoisomerization of the retinal chromophore and explored the implications of preferred direction of torsion 2u or 1u of the chromophore upon the photoexcitation. [19] In this work, we will apply the QTAIM/stress tensor analysis to a different photodriven system, the 9-[(2R)22,4,7-trimethyl-1indanylidene]fluorene light-driven molecular rotary motor (1).…”
Section: Introductionmentioning
confidence: 99%